Makerere University as a Flagship Institution: Sustaining the Quest for Relevance - Bisaso, Ronald (Palgrave Macmillan, Cham, 2017)
Makerere University is an interesting case of a traditional university in sub-Saharan Africa. Such universities were established as both national and regional symbols with the main objective of human resource capacity development. Makerere University transformed from a colonial university to a nationalist university, and is, at present, a neoliberal university (Eisemon, 1994; Mamdani, 2008; Musisi, 2003; Obong, 2004). At each stage of transformation of Makerere University as a flagship institution, emphasis on capacity building for human resources, research productivity to contribute to socioeconomic development, and policy development has been evident.